KOMPETENSI KEPRIBADIAN GURU DALAM MENERAPKAN KARAKTER DISIPLIN - Dzikri Khoirul Haq; Ratna Sari Dewi; Ana Nurhasanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research is based on the importance of teacher competence, including personality competence as a role model in applying the character of discipline. That way, this research has a goal of how the teacher's personality competence in applying the character of discipline, especially the process of strengthening the character of discipline in students through giving examples in learning activities, supporting factors and inhibiting factors for strengthening the character of discipline in students, and the discipline character of students in MI Mambul Hikam Binglu after giving the example. The data collection tools used are observation, interviews, and documentation as well as descriptive analysis. In general, the results of the research show that the Teacher's Personality Competence in Applying Disciplined Characters in Class IV MI Mambaul Hikam Binglu is good. In addition, the supporting and inhibiting factors for strengthening the character of discipline carried out by resource persons at the school indicate that there are several influencing factors, one of which is parents who are able to work well together. However, some parents have not been able to properly monitor the tasks given. For the disciplined character of students after giving an example by the fourth grade teacher, it is quite good.